2014
DOI: 10.1007/s12206-014-0119-1
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study of blowing and suction slot geometry optimization on NACA 0012 airfoil

Abstract: The effects of jet width on blowing and suction flow control were evaluated for a NACA 0012 airfoil. RANS equations were employed in conjunction with a Menter's shear stress turbulent model. Tangential and perpendicular blowing at the trailing edge and perpendicular suction at the leading edge were applied on the airfoil upper surface. The jet widths were varied from 1.5% to 4% of the chord length, and the jet velocity was 0.3 and 0.5 of the free-stream velocity. Results of this study demonstrated that when th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
1
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 24 publications
1
45
1
5
Order By: Relevance
“…Predetermined active flow control includes uniform and non-uniform energy expenditure, regardless of the state of the flow. Reactive flow control is a particular active flow control in which the power expenditure of controllers is regularly tuned by measured parameters via in situ sensors [8,[16][17].…”
Section: Boundary Layer Control Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Predetermined active flow control includes uniform and non-uniform energy expenditure, regardless of the state of the flow. Reactive flow control is a particular active flow control in which the power expenditure of controllers is regularly tuned by measured parameters via in situ sensors [8,[16][17].…”
Section: Boundary Layer Control Methodsmentioning
confidence: 99%
“…The blowing at the trailing edge, however, can enhance the lift, particularly by using smaller oscillation range. Hence, perpendicular suction at the leading edge and tangential blowing at the trailing edge are the best locations for suction and blowing jet slots [17,[24][25].…”
Section: Closing Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…Kianoosh et al [21] observed that when a suction perpendicular to the ow is used, not only does the L/D ratio improve but the stall angle also increases, in the case of a NACA 0012 airfoil the stall angle improved from 14 0 to 22 0 . The hole width also had a direct e ect on the L/D ratio, where the increase in the hole width augmented the L/D ratio and delayed the separation further downstream [21].…”
Section: ''""mentioning
confidence: 99%